Potencial de produtividade e influência do manejo nas lacunas de produtividade de mandioca no Rio Grande do Sul - Freitas, Charles Patrick de Oliveira de (2024)
Cassava plays a fundamental role in agriculture and food security in various regions of the world due to its nutritional value and versatility of uses (human food, animal feed, and industry). For these reasons, it has been recognized as the food of the 21st century by the FAO's "Save and Grow: Cassava" project. Its roots are known for their high carbohydrate content, while its leaves are valued for their high protein content. Rio Grande do Sul is one of the main cassava producers in the country; however, its average productivity (16.8 Mg ha-1 over the last 5 years) is well below the estimated potential productivity of 48.3 to 60.0 Mg ha-1. The objectives of this study were: (i) to estimate the potential productivity of cassava in Rio Grande do Sul; (ii) to estimate the productivity gaps of cassava in Rio Grande do Sul; (iii) to identify the economically viable productivity of cassava in a subtropical environment; and (iv) to validate the management factors that cause the management gap in cassava cultivation in Rio Grande do Sul. To determine the potential and productivity gaps, the methodology used by the Global Yield Gap Atlas (GYGA), which is applied worldwide to various crops, including cassava, was adopted. The estimated productivity potential for Rio Grande do Sul was 54.7 Mg ha-1, showing a productivity gap of 39.4 Mg ha-1, corresponding to 72% of the potential. To achieve economically viable productivity, there is an exploitable productivity gap of 26.6 Mg ha-1, and closing this gap could almost triple the current production in Rio Grande do Sul. The validation of management factors, through the adoption of "Simanihot management," resulted in an increase of 8.0 Mg ha-1 in average productivity.